Підвищення рівня інноваційності національної економіки: правові питання та стратегічні напрями - Подрез-Ряполова, І. (НДІ ПЗІР НАПрН України, 2023)
У науковій роботі досліджені загальні правові аспекти та стратегічні напрями підвищення рівня інноваційності національної економіки, в тому числі розглянуті окремі питання вдосконалення чинного законодавства у сфері інноваційної діяльності. Авторкою статті проаналізовані положення Стратегії розвитку сфери інноваційної діяльності на період до 2030 року. Встановлено, що у Стратегії розвитку сфери інноваційної діяльності на період до 2030 року регламентована потреба у підвищенні рівня інноваційності національної економіки із визначенням відправних орієнтирів щодо забезпечення розбудови інноваційної економіки та національної інноваційної системи. Поряд з цим, у Стратегії розвитку сфери інноваційної діяльності на період до 2030 року визначені проблеми функціонування національної інноваційної системи, зокрема, недостатність фінансування та законодавчого забезпечення, обмеженість фінансових, матеріальних, інформаційних та інвестиційних ресурсів. У статті зазначено, що для того, щоб підвищити рівень інноваційного розвитку національної економіки, необхідно здійснювати комплексні заходи стратегічного, економічного та нормативно-правового спрямування. Доведено, що чинне інноваційне законодавство потребує конструктивного оновлення. Підкреслено, що сучасний економічний стан країни створює нові виклики для провадження інвестиційної діяльності та потребує переходу на нову інноваційну модель. У роботі зроблений висновок, що для сталого розвитку інноваційної національної економіки необхідно забезпечити сприятливі умови для провадження інноваційної діяльності, розвитку національної інноваційної системи та формування привабливого інвестиційного клімату. Problem setting. The development of the national economy in an innovative way in modern conditions is complicated by the presence of internal and external negative factors of influence. The state of war significantly changed the requirements for the implementation of innovative activities, as a result of which the problem of forced adaptation to new conditions arose. Therefore, the issue of ensuring a favorable climate for the stimulation and development of innovative activity, the accumulation of investment resources, and the implementation of a set of effective measures to increase the level of innovativeness of the national economy are relevant today. Analysis of recent researches and publications. The issue of legal support for the stimulation of innovative activity and the problem of innovative development of the national economy of Ukraine is the subject of research by many scientists. S. V. Hlibko considered the issue of legal support for the national innovation system and the innovation process. O. V. Rozghon researched the types and organizational forms of technology transfer in the innovation process. Problematic issues of legal regulation of priority areas of innovative activity in Ukraine were considered by Iu. V. Georgiievskyi. Questions regarding the innovative development of the national economy were mostly investigated by economist’s scientists. However, today’s realities, which reflect significant structural changes at all levels of the economic system and changes in the conditions for the implementation of innovative activities, require additional conceptual studies of the indicated problematic issues. Target of the research is to study the current legal aspects and strategic factors of enhancing the innovativeness of the national economy, including the study of certain issues related to improvement of current legislation in the field of innovation. Article’s main body. The provisions of the main strategic document regarding the implementation of the development of innovative activities provide for the need to increase the level of innovativeness of the national economy with the definition of starting points for ensuring the development of the innovative economy and the national innovation ecosystem. In order to increase the level of innovative development of the national economy, it is necessary to implement complex measures of strategic, economic, regulatory and social direction, Ukraine has a great potential for innovative transformations, and therefore its use will lead to the activation of investment activities and improvement of the functioning of the country’s economic system. Innovation policy should be focused on creating favorable conditions for the development of innovative activities. Today, the main law establishing forms of state stimulation of innovative processes and aimed at supporting the development of Ukraine’s economy in an innovative way needs a constructive update. The system of legal means of ensuring innovation activities (including infrastructural support of the innovation process in the national innovation system) is of decisive importance in terms of increasing the level of innovativeness of the economy. Conclusions and prospects for the development. As a result of the conducted research, it can be concluded that the basis of increasing the level of innovativeness of the national economy in modern conditions is the implementation of the relevant legislatively planned areas and the implementation of complex measures of strategic, economic and legal direction. For the sustainable development of the innovative national economy, it is necessary to provide favorable conditions for the implementation of innovative activities, the development of the national innovation system, and the formation of an attractive investment climate.
Keywords: інноваційна діяльність; інноваційний процес; національна економіка; innovative activity; innovative process; investments; national economy